Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

y = -3x + 13
y = -x + 1
solve by substitution


Sagot :

Answer:

x = 6

y = -5

Explanation:

  • y = -3x + 13
  • y = -x + 1

substitute each of the following,

-3x + 13  = -x + 1

-3x + x = 1 - 13

-2x = -12

x = 6

Find y,

y = -x + 1

y = -6 + 1

y = -5

Step-by-step explanation:

please mark me as brainlest

View image bdilsai06